Onde está a paisagem nas políticas ambientais e territoriais do México? - Martín Manuel Checa-Artasu (Confins)
In Mexico, the study of landscape as a concept and its use as a tool to the analysis of territorial and environmental public policies is still very scarce. Despite this, in recent years different books and articles have been published and different academic meetings have been held that have tried to put the landscape as an element of debate from different disciplines such as social and design sciences and humanities.Far from this debate the decision makers of public policies of the previous government articulated some proposals, such as the "Strategy towards 2040" of the National Commission of Natural Protected Areas or the modification of the General Law of ecological balance and protection to the environment would have opened the possibility of nominating biocultural landscapes as a protected natural area. Sadly, these proposals have been stopped with the arrival of Lopez Obrador’s new government. These proposals apparently made the landscape an analytical and public management object but unfortunately, were disconnected from the contemporary theory of the landscape, from research inquiries made at the academy and even had a doubtful legal and operational applicability. The result all of this is that the landscape remains one of the great forgotten concepts in the environmental and territorial policies of Mexico, despite the serious territorial problems that the country has. Besides, the landscape still has a very insufficient legal consideration. The present paper wants to emphasize the causes of the exclusion of the landscape. This is reflected in a scarce culture of the landscape that is visible in many aspects, and that requires urgent strategies in education, in the revaluation of landscape architecture and in the analysis of the territorial conflicts. These strategies should allow the correct implementation of the landscape as a concept and as a management element in the environmental and territorial public policies of Mexico.